2004
DOI: 10.4161/cc.3.10.1166
|View full text |Cite
|
Sign up to set email alerts
|

JNK is Associated with Bcl-2 and PP1 in Mitochondria: Paclitaxel Induces Its Activation and Its Association with the Phosphorylated Form of Bcl-2

Abstract: It has been shown that the activation of JNK after paclitaxel-induced microtubule damage is parallel to Bcl-2 phosphorylation, cell cycle arrest in mitosis and apoptosis. Using subcellular fractionation and immunocytochemistry, we found here that a pool of activated JNK is located in mitochondria of HeLa cells treated with paclitaxel. Furthermore, whereas the JNK protein is present in a tripartite complex with the anti-apoptotic Bcl-2 protein and the PP1 phosphatase in mitochondria isolated from control cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 35 publications
2
41
0
1
Order By: Relevance
“…This highlights a yetunknown PP1-dependent cross talk between MAPK and JNK pathways that may operate a few hours after injury (not observed 1 h after OGD in vitro). The ability of PP1 to associate with JNK2 in a tripartite complex in mitochondria may underlie this feature, and provide a means to tightly control this interaction (Brichese et al, 2004). Moreover, the concomitant activation of ERK1/2 and JNK2 may exacerbate the impact of excitotoxicity by activating the protease caspase-3.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights a yetunknown PP1-dependent cross talk between MAPK and JNK pathways that may operate a few hours after injury (not observed 1 h after OGD in vitro). The ability of PP1 to associate with JNK2 in a tripartite complex in mitochondria may underlie this feature, and provide a means to tightly control this interaction (Brichese et al, 2004). Moreover, the concomitant activation of ERK1/2 and JNK2 may exacerbate the impact of excitotoxicity by activating the protease caspase-3.…”
Section: Discussionmentioning
confidence: 99%
“…Different reports have suggested that the phosphorylation of anti-apoptotic protein Bcl-2 and Bcl-xL regulated their stability (43, 45, 46) and, possibly, their addressing to mitochondria (47). The Akt/PKB-dependent regulation of the function of BH3-only protein Bad is now well established (48).…”
Section: Modulation Of Bax Function Bymentioning
confidence: 99%
“…Therefore, mitochondria protein phosphorylation will also most likely be regulated by mitochondria-targeted protein phosphatases. Although Protein Phosphatase 1(PP1) and PP2A have been found in mitochondria (Ruvolo et al 2002;Dagda et al 2003;Brichese et al 2004;Tamura et al 2004), their specific contribution to the mitochondrial function remains unclear. Recently, a novel tyrosine protein phosphatase, PTPMT1, was reported to be located specifically in the mitochondria matrix and to play an important role in both ATP production and insulin secretion (Pagliarini et al 2005), further supporting the notion that protein phosphorylation and dephosphorylation in mitochondria are an important mechanism of cell signaling.…”
mentioning
confidence: 99%
“…Further, both PKC and PKC␦ have been implicated in mitochondrial K ATP channel regulation in ischemic preconditioning (Cohen et al 2000;Chen et al 2001). Finally, ERK and JNK kinases are targeted to mitochondria to phosphorylate apoptotic proteins, including Bcl-xl, Bcl-2, and BAD, and regulate apoptosis (Deng et al 2000;Kang et al 2003;Schroeter et al 2003;Brichese et al 2004). In short, Ser/Thr protein kinase targeting to mitochondria has significant impact on pro-or anti-apoptotic factors, respiration, and ionic channel activity, illustrating the important role of mitochondria protein phosphorylation in cellular signaling.…”
mentioning
confidence: 99%